PENGARUH MEDIA MOLYIKOV TERHADAP HASIL BELAJAR MATERI IKATAN KOVALEN KELAS X SMAN 1 MELIAU - Bernadif, Imam; Enawaty, Eny; Sartika, Rody Putra (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe aims of this research is to know the difference and how much influence of learning process using molyikov  to student learning outcomes on covalent bonding material. The population of this study is all students of grade X IPA SMA Negeri 1 Meliau academic year 2017/2018. The sampling technique used is saturated sampling. Data collecting techniques used are measurement techniques and direct communication techniques. Instrument assessment used is the test of learning outcomes. The sample used in this research is class X IPA 1 as control class and class X IPA 2 as experiment class. The design used in this research is control group pretest-posttest design. The results showed statistical test of U Mann-Whitney Gain Score test, giving Sig value. (2-tailed) = 0,000 <0,05 which states Ho is rejected means that there are differences in learning outcomes between control class students given learning without using molyikov media and experimental class given learning by using molyikov media. The influence of learning using molyikov media gives 35.54% influence on learning outcomes in covalent bond material of grade X SMA Negeri 1 Meliau students. Keywords: molyikov, learning outcomes, covalent bonds.